Peningkatan Kandungan Alkaloid Kalus Mahkota Dewa (Phaleria macrocarpa [Scheff.]Boerl.) Dengan Pemberian Prekursor Triptofan pada Medium Murashige & skoog - Wenny Rahma Gusni; Suwirmen Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2015)
An experiment aimed to increase alkaloid content of Phaleria macrocarpa callus using tryptophan as a precursor in Murashige & Skoog media was done from September 2013 to January 2014 at the Laboratory of Plant Physiology, Faculty of Sciences, Andalas University. This experiment used Completely Randomized Design (CRD) with 6 treatments and 4 replications. The treatments were 6 consentrations of tryptophan i.e.0 mg/L (control), 100 mg/L, 125 mg/L, 150 mg/L, 175 mg/L, 200 mg/L. The results showed that tryptophan 200 mg/L gave the best concentration in producing the highest alkaloid content of Phaleria macrocarpa callus.